Estrategias de acompañamiento pedagógico, en el proceso de enseñanza, de los docentes de básica superior del colegio Machala, del cantón Machala, de la provincia de El Oro; durante el período: 2023-2024. - Arboleda Macas, Tomas Javier (2023)
The present academic work about: pedagogical accompaniment strategies, in the teaching process, in upper basic teachers; It has been justified considering that the education of children and youth is essential for the development of society. Hence the importance of the study; considering that the role of the pedagogical advisor or inspector and the strategies used for the pedagogical accompaniment of the teacher, are decisive to achieve the objectives of education in our region and country. The purpose of the research has been to determine how the application of pedagogical accompaniment strategies affects the teaching process of upper basic teachers; in order to strengthen a culture of improvement and innovation of pedagogical practice. A non-experimental research design with a descriptive level and a mixed approach was employed, and due to its duration in implementation, it was cross-sectional. Techniques such as: interviews, surveys, and documentary review were used to collect information; the same that was processed and analyzed, using the spss program; to find the results. Keywords: pedagogical strategies, teaching-learning, support strategies, pedagogical support workshops